Investigation of wild relatives of cultivated plants of Aktubinsk floristic region (Eurasian Journal of Ecology, 2018)
The aim of investigation is to identify the species composition andtheir ecological properties of wild relatives of cultivated plants of Aktobefloristic region. At the article the analysis of species composition and degree of perspectives of wild relatives of cultivated plants. As result of cameral literature and field investigation the list of wild relatives of cultivatedplants of present region was 153 species from 81 genes and 22 families.The biggest amount of wild relatives of cultivated plants is noted in familiesPoaceae (43 species), Fabaceae (39 species), Chenopodiaceae (20 species)and Asteraceae (12 species). The analysis of priority of wild relatives ofcultivated plants has allowed to distribute plants as follows: to the 1st group(the species which are directly presented in culture and have grades) – 32species; to the 2nd group (the species which are directly participating incrossings, used as sources of genes or stocks) – 2 species; to the 3rd group(species close relationship with entered into culture (as a part of one section or a sub-sort), perspective for economic use) – 19 species; to the 4thgroup (other useful species used in collecting and national selection) – 2species; to the 5th group (all other species of present genus) – 98 species.Key words: ecology, Aktubinsk floristic region, flora, perspectives,practical properties, wild relatives of cultivated plants.